Effect of miR-25 on Proliferation of Nasopharyngeal Carcinoma Cells through Wnt/β-Catenin Signaling Pathway. (27th August 2021) - He, Haixia; Yuan, Kun; Chen, Wei
Abstract : Objective . To investigate the biological role and potential mechanism of miR-25 in nasopharyngeal carcinoma. Methods . The expression of miR-25 in nasopharyngeal carcinoma cell lines was detected by qRT-PCR. The effect of inhibition of miR-25 expression on the proliferative activity of nasopharyngeal carcinoma cell line HONE-1 was examined by CCK-8 method. Flow cytometry was used to detect the effect of miR-25 expression inhibition on the apoptosis rate of nasopharyngeal carcinoma cell line HONE-1. The miRNA target gene prediction site TargetScan predicts the target protein action site of miR-124 and verifies whether miR-25 interacts with the target by luciferase activity assay, qPCR, and Western experiments. The miR-25 inhibitor and target egg gene expression plasmids were cotransfected into HONE-1 cells for rescue experiments to investigate whether miR-25 inhibits proliferation of nasopharyngeal carcinoma cells by target genes. At the same time, qRT-PCR was used to detect the mRNA expression levels of Wnt/ β -catenin pathway key proteins TCF4, c-Myc, and Cyclin D1 in different transfected cells. Results . miR-25 expression was upregulated in nasopharyngeal carcinoma cell lines. Functional studies showed that inhibition of miR-25 expression significantly inhibited the proliferation of nasopharyngeal carcinoma cell line HONE-1 (p < 0.05 ). Inhibition of miR-25 expression by flow cytometry significantly promoted apoptosis (p < 0.05 ). Detection of dual luciferase activity indicated that DKK3 is a direct target site for miR-25. Western blots showed that inhibition of miR-25 significantly upregulated DKK3 mRNA and protein levels. Supplementation with DKK3 significantly attenuated the inhibitory effect of miR-25 on the proliferation of nasopharyngeal carcinoma cell line HONE-1 (p < 0.05 ). qRT-PCR found that mRNA levels of TCF4, c-Myc, and Cyclin D1 were significantly upregulated in miR-25-transfected cells compared to control transfection. QRT PCR showed that the mRNA and protein levels of Tcf4, c-myc, and Cyclin D1 were significantly upregulated in miR-25 overexpression-transfected cells. Conclusion . Inhibition of miR-25 expression promotes DKK3 gene expression, and inactivation of Wnt/ β -catenin signaling pathway inhibits proliferation and promotes apoptosis of nasopharyngeal carcinoma cells.